Exploring professional competencies of college librarians in Sahiwal division, Pakistan. - Muhammad Kabir Khan , Muhammad Imran & Arslan Sheikh (IJoLIS, 2024)
Purpose- The goal of this study was to investigate the professional competencies of private college librarians in the Sahiwal Division. Research Methodology- In this study, a survey-based quantitative research strategy was employed. A questionnaire as a research tool was used to collect data from college librarians of Sahiwal Division. The population of the study comprised male and female professional librarians and library staff working at different private colleges in the Sahiwal Division. A total of 101 registered private colleges were selected as the population whereas the estimated number of library professionals in all these colleges came to 101 librarians. The convenience sampling technique was used in the study.